2015
DOI: 10.1007/s10972-015-9428-1
|View full text |Cite
|
Sign up to set email alerts
|

Student Teachers’ Approaches to Teaching Biological Evolution

Abstract: Evolution is fundamental to biology and scientific literacy, but teaching high school evolution is often difficult. Evolution teachers face several challenges including limited content knowledge, personal conflicts with evolution, expectations of resistance, concerns about students' conflicts with religion, and curricular constraints. Evolution teaching can be particularly challenging for student teachers who are just beginning to gain pedagogical knowledge and pedagogical content knowledge related to evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 51 publications
0
25
0
1
Order By: Relevance
“…Even for teachers who accept evolution, many teachers’ refusals to teach evolution are due to pressure (from administrators, school board members, colleagues, parents, clergy, other community members, and students themselves); negative attitudes and mixed messages from state and local leaders; state, district, and school guidelines, standards, and exams for teaching evolution; actual or perceived support within the school itself for teaching evolution; their awareness of the attitudes toward the importance and teaching of evolution in their communities; their positions in their respective professional communities; their ideas about teaching and learning; unfamiliarity with laws about teaching evolution and creationism in science classrooms; lack of time; lack of knowledge, training, and preparation to teach evolution; lack of awareness of available instructional resources; and their own evolution learning experiences (Aguillard, 1998; Van Koevering and Stiehl, 1989; McGinnis and Simmons, ; Chuang, ; Brem et al, ; Griffith and Brem, ; Moore, ; Lazarowitz and Bloch, ; Moore and Kraemer, ; National Science Teachers Association, ; Asghar et al, ; Sanders and Ngxola, ; Goldston and Kyzer, ; Dotger et al, ; Fowler and Meisels, ; Nadelson and Nadelson, ; Nadelson and Sinatra, ; Bramschreiber, ; Hermann, ; Berkman and Plutzer, ; Borgerding et al, ; Glaze et al, ). In a study of Ohio high school biology teachers, 10% had been pressured not to teach evolution, and 11% had received pressure to teach creationism (Zimmerman, 1987).…”
Section: Obstacles To Teaching and Learning Evolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even for teachers who accept evolution, many teachers’ refusals to teach evolution are due to pressure (from administrators, school board members, colleagues, parents, clergy, other community members, and students themselves); negative attitudes and mixed messages from state and local leaders; state, district, and school guidelines, standards, and exams for teaching evolution; actual or perceived support within the school itself for teaching evolution; their awareness of the attitudes toward the importance and teaching of evolution in their communities; their positions in their respective professional communities; their ideas about teaching and learning; unfamiliarity with laws about teaching evolution and creationism in science classrooms; lack of time; lack of knowledge, training, and preparation to teach evolution; lack of awareness of available instructional resources; and their own evolution learning experiences (Aguillard, 1998; Van Koevering and Stiehl, 1989; McGinnis and Simmons, ; Chuang, ; Brem et al, ; Griffith and Brem, ; Moore, ; Lazarowitz and Bloch, ; Moore and Kraemer, ; National Science Teachers Association, ; Asghar et al, ; Sanders and Ngxola, ; Goldston and Kyzer, ; Dotger et al, ; Fowler and Meisels, ; Nadelson and Nadelson, ; Nadelson and Sinatra, ; Bramschreiber, ; Hermann, ; Berkman and Plutzer, ; Borgerding et al, ; Glaze et al, ). In a study of Ohio high school biology teachers, 10% had been pressured not to teach evolution, and 11% had received pressure to teach creationism (Zimmerman, 1987).…”
Section: Obstacles To Teaching and Learning Evolutionmentioning
confidence: 99%
“…Bramschreiber () notes that every teacher in his study—which took place in an area with pervasive anti‐evolution sentiment—felt unprepared for resistance they would face and received no formal training in this area from their teacher preparation programs. Even pre‐service teachers are already thinking about how they will deal with evolution in their own classrooms and report feeling pressure to teach or not teach it (Van Koevering and Stiehl, 1989; Borgerding et al, ; Glaze et al, ). In a study of pre‐service teachers, Borgerding et al () found that cooperating (mentor) teachers had a strong influence on evolution instruction via planning, pressuring for test preparation, and guiding how the relationship between religion and science was addressed; one teacher described how his cooperating teacher even urged him not to compassionately address his students’ religious tensions.…”
Section: Obstacles To Teaching and Learning Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet elementary through postsecondary students, and the general public, have a poor grasp of this essential science idea (reviewed in Gregory 2009). Research has documented that evolution is difficult to teach and learn (Borgerding et al 2015). A national assessment of students' ideas about evolution and natural selection found that misconceptions related to common ancestry were among the most prevalent (Flanagan and Roseman 2011).…”
Section: Introductionmentioning
confidence: 99%